2009
DOI: 10.1111/j.1743-6109.2009.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Gene Intron 4 VNTR and Exon 7-G894T Polymorphisms in Turkish Men with Erectile Dysfunction: A Case Control Study

Abstract: Introduction The associations between the gene polymorphisms and erectile dysfunction (ED) are limited. Aim To examine a potential association between variable number of tandem repeats (intron 4 VNTR), G894T polymorphisms, and ED in Turkish men. Methods Sixty-four men with ED and 82 healthy men as a control group were included in the study. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Although functional experiments support the involvement of eNOS in the pathogenesis of ED [18], results of association studies regarding the relationship between eNOS variants and ED risk have remained inconsistent. More specifically, it has been reported that 894T allele carriers were associated with an increased risk of ED in Mexican and Turkish populations [19,20]. Another study conducted in Germany, however, showed no significant relationship between G894T polymorphism and ED [21].…”
Section: Introductionmentioning
confidence: 98%
“…Although functional experiments support the involvement of eNOS in the pathogenesis of ED [18], results of association studies regarding the relationship between eNOS variants and ED risk have remained inconsistent. More specifically, it has been reported that 894T allele carriers were associated with an increased risk of ED in Mexican and Turkish populations [19,20]. Another study conducted in Germany, however, showed no significant relationship between G894T polymorphism and ED [21].…”
Section: Introductionmentioning
confidence: 98%
“…Besides, 2 low-quality studies were also excluded ( Figure 1 ). Finally, 12 studies were enrolled into our meta-analysis 22526373839404142434445. The subjects in these 12 studies were Asians (5 studies) and Caucasians (7 studies), and the studies contained a combined total of 1962 ED patients and 1752 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of eNOS enzyme activity in T allele carriers revealed 20% lower activity compared to individuals homozygous for the G allele 26. Erectile function depends on the relaxation and contraction of penis which is regulated by smooth muscle, and G894T polymorphism was found to interfere with this process, increasing ED predisposition 41. The two SNPs (T-786C and G894T) variously affect either eNOS transcription rate or its enzyme activity to dramatically reduce NO production, resulting in decreased functioning of the eNOS/NO system to buffer blood pressure fluctuations 21.…”
Section: Discussionmentioning
confidence: 97%
“…Polymorphisms in eNOS gene have been hypothesized to be associated with erectile complaints. A polymorphism located in exon 7 of the eNOS gene (G894T) has been the focus of a number of studies regarding the influence of eNOS on ED susceptibility [24,30–32]. The T allele, which results in a substitution of aspartate for glutamate at amino acid position 298 of eNOS, has been associated with a significantly higher risk of ED in Mexican, Taiwanese, Turkish, and Iranian populations [24,30–33].…”
Section: Resultsmentioning
confidence: 99%